The Influence Of Transformational Leadership, Interpersonal Communication, And Service Quality On Organizational Commitment Of Teachers At Sun Education Group - Sari Nidaul Hasanah; Lili Nurlaili; Surasni Surasni (Universitas Pakuan, 2026)
Education is the lifeblood of a nation's progress, as without quality education, the sustainability and future of a nation will be threatened. In this context, teacher commitment plays a highly strategic role in improving service quality and learning outcomes. However, in practice, transformational leadership implemented by leaders or superiors often tends to focus on strict rules, is less adaptive to dynamic work environment changes, and has not been able to provide optimal interpersonal communication for teachers and employees. This condition has resulted in declining service quality and organizational commitment of teachers and employees at Sun Education Group, which ultimately has implications for their service quality. This research aims to analyze the influence of transformational leadership on interpersonal communication, service quality, and organizational commitment at Sun Education Group throughout Indonesia. A quantitative research approach is used with survey techniques through the distribution of questionnaires to teachers and employees in their respective regions. Data is analyzed using regression methods to determine the relationships and influences between variables. The research results are expected to provide an empirical overview of the extent to which transformational leadership contributes to the improvement or decline of interpersonal communication, service quality, and organizational commitment at Sun Education Group. These findings are also expected to serve as considerations for teachers and policymakers in determining a more effective leadership model for improving service quality and organizational commitment at Sun Education Group.